ANALISIS PENDAPATAN DAN EFISIENSI USAHATANI PADI SAWAH DI DESA KOTA BANGUN KECAMATAN KOTA BANGUN - Tino Margi; Siti Balkis (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The objective of this research was to determine the lowland rice farm income and knowing the lowland rice farm income of farmers in Kota Bangun I Village, Kota Bangun sub District, Kutai Kartanegara District. This research started on July until September 2013, with research location is in Kota Bangun I Village, Kota Bangun sub District, Kutai Kartanegara District.. The method that used is simple random sampling method. The data needed by research are primary and secondary data. Primary data is got by observation and interview with responder use questionnaire which have been compiled in line with research.  While secondary data is got from bibliography study and institution information which is related to research execution. The results of this research shows that : Average of production cost of lowland rice plantation to one season was Rp 242.032.750,00 mt-1 or Rp 6.050.819,00 mt-1 respondent-1.Total revenue farmers was Rp 950.836.000,00  mt-1 or Rp 23.770.900,00 mt-1 respondent-1 and average farm income is Rp 708.803.250,00  mt-1 or Rp 17.720.081,00 respondent-1.Value of R/C ratio was 3,87 meaning that the cultivated lowland rice farm is already profitable then planting a lowland rice can for resumes.